1991
DOI: 10.2527/1991.692755x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutritional deprivation on insulin-like growth factor I, somatotropin, and metabolic hormones in swine.

Abstract: Although growth hormone (GH) is a primary stimulus for the synthesis of insulin-like growth factor I (IGF-I), other factors such as nutritional status, insulin, and thyroid hormones are important modulators of circulating IGF-I levels. Thus, the effects of feed restriction and subsequent refeeding on plasma levels of IGF-I, GH, insulin, and thyroid hormones were studied in swine. Despite an elevation in plasma GH levels after 48 h of feed restriction, circulating IGF-I levels were decreased by 53% (P less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
53
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 0 publications
12
53
0
1
Order By: Relevance
“…In many experimental models food restriction is associated with reduced skeletal growth, with such association primarily resulting from impaired growth hormone action (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In a previous study we demonstrated that mice undergoing 4 weeks of food restriction exhibited increased expression of Fgf21 (both in the liver and in the growth plate), growth hormone (GH) 3 insensitivity, and a concomitant reduction of their body linear growth and growth plate chondrogenesis (17).…”
mentioning
confidence: 99%
“…In many experimental models food restriction is associated with reduced skeletal growth, with such association primarily resulting from impaired growth hormone action (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In a previous study we demonstrated that mice undergoing 4 weeks of food restriction exhibited increased expression of Fgf21 (both in the liver and in the growth plate), growth hormone (GH) 3 insensitivity, and a concomitant reduction of their body linear growth and growth plate chondrogenesis (17).…”
mentioning
confidence: 99%
“…IGF-I levels were lower in L than in H sows during lactation despite slightly higher GH levels, which suggests an uncoupling of IGF-I secretion from GH secretion under nutrient deficit, as observed in restricted growing pigs [11] and in lactating cows [44]. In well-fed multiparous sows, Schams et al [45] suggested that the uncoupling between IGF-I and GH secretions was absent.…”
Section: Metabolic Hormonesmentioning
confidence: 97%
“…During periods of nutritional deficit GH concentrations are elevated in several species including the pig [15], sheep [88] and cow [11], reflecting the effects of factors such as hypoglycemia and stress on pituitary secretion of GH. Gluckman and Breier [35] observed an increase in GH pulse amplitude in steers fed at 1% dry matter (DM) in comparison with steers fed at 3% DM of live weight of a high concentrate diet.…”
Section: Effect Of Nutritional Status On Circulat-ing Concentrations mentioning
confidence: 99%